Handbook of research on technoethics [ - Adell, Rebecca; Luppicini, Rocci (Information Science Reference, 2009)
"This book traces the emergence of the new interdisciplinary field of technoethics by exploring its conceptual development, important issues, and key areas of current research. Compiling 50 authoritative articles from leading researchers on the ethical dimensions of new technologies"--Provided by publisher.